2009
DOI: 10.1007/s00268-009-0303-0
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Trial for Papillary Thyroid Microcarcinoma in Japanese Patients

Abstract: Background The recent development and spread of ultrasonography and ultrasonography-guided fine needle aspiration biopsy (FNAB) has facilitated the detection of small papillary microcarcinomas of the thyroid measuring 1 cm or less (PMC). The marked difference in prevalence between clinical thyroid carcinoma and PMC detected on mass screening prompted us to observe PMC unless the lesion shows unfavorable features, such as location adjacent to the trachea or on the dorsal surface of the thyroid possibly invading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
588
2
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 701 publications
(624 citation statements)
references
References 31 publications
16
588
2
18
Order By: Relevance
“…Moreover, we published the results of another, more-recent observation trial in 2010, in which tumor enlargement and novel appearance of node metastasis were detected only in 6.5% and 1.4% of patients after 5 years of observation, respectively. 4 Importantly, none of the patients who underwent surgery after observation showed postoperative carcinoma recurrence and none of the patients who underwent observation showed distant metastasis or died of thyroid carcinoma.…”
Section: Yasuhiro Ito and Akira Miyauchimentioning
confidence: 97%
“…Moreover, we published the results of another, more-recent observation trial in 2010, in which tumor enlargement and novel appearance of node metastasis were detected only in 6.5% and 1.4% of patients after 5 years of observation, respectively. 4 Importantly, none of the patients who underwent surgery after observation showed postoperative carcinoma recurrence and none of the patients who underwent observation showed distant metastasis or died of thyroid carcinoma.…”
Section: Yasuhiro Ito and Akira Miyauchimentioning
confidence: 97%
“…Finally, some authors are highlighting worldwide that papillary thyroid microcarcinoma (PTMC) often represents a very low-risk lesion of indolent course, for which total thyroidectomy might be a very aggressive therapeutic choice [49][50][51]. Although current pieces of scientific evidence and experts' opinions do not allow us to treat these lesions in a nonsurgical, conservative fashion [52,53], we can suppose that in the near future, US-guided techniques might play a role also in primary PTMC, when no multifocality or nodal metastasis was found, offering patients a less aggressive therapeutic option without reducing the clinical outcomes and the very high rate of disease-free survival.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Often these are microcarcinomas that are not detected on preoperative imaging. In addition, some observational studies have shown very low progression rates (16). Nevertheless, it is important for clinicians to realize that after a lobectomy, 25% of these patients will have contralateral cancer foci.…”
Section: Figmentioning
confidence: 99%